William chambers: British army surgeon (Toulon, 1793) and his vaccination institution (1803) in Brighton, England. (November 2022) - Cooper, Maxwell J; Whiston, Benjamin
Following Edward Jenner's research into cowpox, a wave of vaccination services emerged across England. Despite some resistance, these began to promote population prevention where variolation had failed. Sussex's first vaccine institution has long been considered to be that of Sir Matthew Tierney (1776–1845). Founded in 1804, Tierney's "Royal Sussex Jennerian Society for the Extermination of the Small-pox" comprised sixteen stations, including one in Kent. This article presents an earlier example: the 1803 "Brighton Royal Jennerian Institution", founded by a "Mr Chambers" to serve "the indigent poor". Given that both held royal and military appointments in Brighton, Tierney must have been aware of Chambers' efforts in vaccination. It is unclear why Tierney's 1804 plan for the Sussex Vaccine Institution makes no mention of Chambers. In 1803 Chambers also directed the establishment of Brighton's first military hospital and is noted as "surgeon extraordinary" to the Prince Regent. Chambers is identified as William Chambers of the 10th Royal Dragoons, who served at Toulon (1793) as a surgeon's mate. He is also documented at Corsica in 1794 where he examined Nelson's injured eye following the siege of Calvi. Mr Chambers' origin and more details of his biography remain unknown.